Bactericidal Activity of Superoxide Anion and of Hydrogen Peroxide: Investigations Employing Dialuric Acid, a Superoxide-Generating Drug - DeChatelet, Lawrence R. (1975)
The addition of dialuric acid (a superoxide-generating drug) to a suspension of resting human neutrophils resulted in a stimulation of cellular hexose monophosphate shunt activity. Measurement of oxygen consumption demonstrated a rapid rate of oxygen uptake by the drug alone in aqueous solution. The subsequent addition of catalase (but not of superoxide dismutase) resulted in a substantial release of oxygen, indicating that H(2)O(2) was accumulating in the media. The generation of O(2)(−) by the drug was verified by measuring the rate of reduction of cytochrome c by the drug in the presence and absence of authentic superoxide dismutase. The growth of Escherichia coli B and Staphylococcus aureus was inhibited in vitro by addition of the drug to a suitable culture media; the degree of inhibition was dose dependent. This inhibition of bacterial growth could be completely reversed by the addition of as little as 5 μg of purified catalase, but was not affected by concentrations of superoxide dismutase that were 2,000-fold higher. These results suggest that the dialuric acid-induced stimulation of hexose monophosphate shunt activity in neutrophils is due to accumulated H(2)O(2). Further, the contribution of superoxide to the bactericidal activity towards E. coli and S. aureus is probably minimal compared with that of H(2)O(2).